Lex localis (Lex localis, 2003)
Lex localis - Journal of Local Self-Government is an international journal for the study of the politics, administration, and management of local affairs published four times a year (in January, April, July, and October) by Institute for Local Self-Government and Public Procurement Maribor (Slovenia).
Keywords: local government; Lokalna samouprava; Slovenia; Slovenija